Transcending health literacy: using videos to aid advance care planning and healthcare decision-making. Issue 2 (1st June 2012) - Vig, C; Berg, B; Simon, J
Abstract : A critical aspect of advance care planning is patient understanding of how goals of care and related medical interventions reflect their values and wishes for current and future healthcare decisions. Research regarding the use of patient education videos portraying resuscitative, medical and comfort care is demonstrating increases in patient understandings of healthcare interventions and the determination of medically appropriate goals of care. The use of goals of care videos assists with transcending health literacy for patients and families involved in healthcare decision making, and highlights the process of engaging in meaningful conversations between families and healthcare providers. This workshop will present a patient education video series that is based on current research development and findings that use videos to improve patient understanding about goals of care. The videos have been created to align with the "Advance Care Planning: Goals of Care Designation (ACP/GCD) (Adult)" policy that was systematically implemented within Alberta Health Services, Calgary Zone in 2008. The series is intended to provide relevant information related to healthcare considerations and blends the questions of 'why engage in ACP?' with 'what are the healthcare interventions to consider?' The two-part video series includes: Understanding Goals of Care and Engaging in Advance Care Planning, These videos will be presented as tools to help bridge the gap between patient values and wishes and beneficial medical interventions, as they relate to the Goals of Care framework adopted by Calgary Zone.